Nursery fertilization of Pithecellobium dulce (Roxb.) Benth: effects on seedling quality - Basave-Villlalobos, Erickson; Cetina-Alcalá, Víctor Manuel; López-López, Miguel Angel; Trejo, Carlos; Ramírez-Herrera, Carlos; Conde-Martínez, Víctor (Instituto de Ecología, A.C., 2020)
Nursery fertilization is a cultural practice with potential to improve seedling quality, but it is necessary to define adequate fertilization levels for each specie. This study evaluated the effect of fertilization levels on seedling quality of Pithecellobium dulce during the nursery stage. The applicated levels were nine; they consisted in regimes in which a controlled-release fertilizer (CRF) 18-6-12, in three doses (4 g L-1, 6 g L-1, and 8 g L-1 of substrate) was mixed with a water-soluble fertilizer (WSF) 20-20-20, in concentrations of nitrogen of 0 mg L-1, 75 mg L-1, and 150 mg L-1. The fertilization regimes effects were determined by assessing morphological attributes of seedling quality, net assimilation rates (NAR), and nutrimental status of N-P-K on four-month old seedlings. A seedling-quality test was designed to undergo the seedlings to a stress condition of both nutrient’s deficiencies and biomass loss, thereby measuring their resprouting capacity and growth. Statistical differences were observed by the effects of the fertilization regimes. Overall, an increase of the morphological quality and NAR was promoted by the mix of 8 g of CRF with 150 mg N L-1 of WSF, although the main responses in relation to the nutrimental status were of deficiency and dilution. In the seedling-quality test, the seedlings had limitations to induce either their resprouting or their growth according to the amount of nutrimental reserves. The fertilization with CRF and WSF have potential to enhance the seedling quality of P. dulce during nursery culture.